Development of a lithium based chicken bone (Li-Cb) composite as an efficient catalyst for biodiesel production - Al Sharifi, M.; Znad, Hussein (Elsevier, 2019)
A lithium based chicken bone (Li-Cb) composite has been synthesized by wet impregnation method followed by calcination at various temperatures (750, 800, 850, and 900?°C). The Li-Cb catalysts were characterized by Field Emission Scanning Electron Microscope (FESEM), Brunauer–Emmett–Teller surface area (BET), X-ray diffraction (XRD), TG-DSC and Fourier-transform infrared spectroscopy (FT-IR). The catalytic activities of Li impregnated catalyst were described in term of basicity. 2 g of LiNO3 impregnated in 7?g of Cb and calcinated at 850?°C (2Li-Cb850) were found as the best combination to synthesize the efficient catalyst for the transesterification of canola oil with 96.6% conversion to FAME in 3?h of reaction time along with 18:1 of methanol:oil molar ratio, catalyst loading of 4?wt %, and reaction temperature of 60?°C. The pseudo-first order model with 0.58 h-1 rate constant (at 60?°C) and 16.9?kJ/mol activation energy was the best fitted to represent the transesterification kinetic. Moreover, the prepared catalyst (2Li-Cb850) showed sustained activity after being recycled and reused for 5 times with FAME content?>?82%.